Design of the Emergency Messages Integration for Vehicle to Everything (V2X) Communications of Connected Cars - Young-Hyun, Eom; Kim, Inhwan; Yoo, Hyunmi; Cho, Sungguk; Jeon, Byungkook (International Journal of Engineering and Technology, 2018)
So far, international standardization of message specifications between V2X(Vehicle to Everything) safety communications are BSM(Basic Safety Message) by US-led SAE and CAM(Cooperative Awareness Message)/DENM(Decentralized Environmental Notification Message) by EU-led ETSI. However, in the emergency situation such as car accidents or road traffic jam, there may be insufficient time to process all messages. In this paper, we propose an integration of emergency messages for V2X communications of connected vehicles in VANETs(Vehicular Ad hoc Networks), To do this, we are using the Mobile Virtual Fence(MVF), which has been preliminarily researched and developed. So we extract and integrate only emergency messages as the fields of similar messages between BSM and CAM/DENM, and apply it to the MVF. If it will be the connected MVFs like connected cars in the future and any traffic accident or traffic jam occurs, the proposed messages will be communicated to each other to avoid the accident. Therefore the proposed integration of emergency messages between BSM and CAM/DENM specification will be contribute to improve the safety and reliability as the unified and integrated emergency messages.Â Â